Correlation Between Knowledge and Practice of Basic Life Support (BLS) Among Nursing Students, Class of 2022, Academic Year 2025 - Jesus Leite, Ana do Rosario de; da Conceicao Alves, Maria Manuela; Deus, Elisa de; Evaristo Obeno, Olandino; Tilman, Carlos Boavida; Almeida Oqui, Serafino de; Selviana Noronha, Maria Muna (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Emergencies can occur anywhere and at any time without warning, making preparedness essential for everyone to know how to respond when faced with life-threatening situations. Basic Life Support (BLS) and Cardiopulmonary Resuscitation (CPR) are critical interventions that can help preserve life in emergency conditions. Objective: This study aims to determine the Correlation Between Knowledge and Practice of Basic Life Support (BLS) Among Nursing Students, Class of 2022, Academic Year 2025. Method: This research employed a quantitative correlational method with a cross-sectional approach. The sampling technique used was non-probability sampling with a total sampling method. Data were collected using a structured questionnaire. Univariate data analysis applied frequency distribution, while bivariate analysis used the Spearman Rank correlation test. Results and Discission: Based on the analysis using the Spearman Rank test, the correlation between the independent variable (BLS knowledge) and the dependent variable (BLS practice) showed a correlation coefficient r = 0.342 with a p-value = 0.000, which is smaller than the significance level of 0.05. This indicates a significant positive Correlation Between Knowledge and Practice of Basic Life Support (BLS) Among Nursing Students, Class of 2022, Academic Year 2025. Conclusion: The findings demonstrate a statistically significant positive Correlation Between Knowledge and Practice of Basic Life Support (BLS) Among Nursing Students, Class of 2022, Academic Year 2025.